Toward a transdisciplinary approach to FL classroom interaction - Ciepiela, Kamila (Yearbook of the Poznan Linguistic Meeting, 2021)
The focus of the article is on the questions and issues that have arisen in research on communication in second language contexts, as well as possibilities of addressing them that open up when one moves to the understanding of scientific inquiry as “a form of anti-disciplinary or transgressive knowledge, as a way of thinking and doing that is always problematizing” (Pennycook 2007: 37). The article aims to point to some issues in research on communication in a FL classroom where a transdisciplinary approach might prove useful or even necessary to address them. An expanded analysis of a classroom discussion carried out within Hymes’ model that includes different modes and forms of communication as well as aspects of on-goingly changing contexts should illustrate the benefits of applying a transdisciplinary approach in research on communication in a second language classroom.